2022
DOI: 10.1002/ceat.202100430
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnO Nanoparticles with Antibacterial Properties Using Terminalia catappa Leaf Extract

Abstract: In order to develop alternative drugs against resistant pathogens, capped ZnO nanoparticles (NPs) were prepared using Terminalia catappa leaf extract. By changes in pH and aging time, cauliflower-like, sheet-like, and hierarchical morphologies for ZnO NPs were obtained. Their antibacterial activities against Staphylococcus aureus and Escherichia coli were investigated. The results demonstrated that the green synthesized ZnO NPs exhibit higher antibacterial activity than chemically prepared ZnO NPs. The antibac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…ROT co-exposed with MK-ZnO NPs demonstrated significantly less blue staining in the tissues mentioned above and the whole larvae when compared to the ROT plus UD-ZnO and ROT plus MC-ZnO NPs groups, respectively. This conclusion is validated by a previous investigation that showed that plant biomolecules significantly enhanced cell viability and attenuated DNA damage [ 79 , 80 ]. Biogenic ZnO-NPs are protective due to the activation of antioxidant defense mechanisms or the presence of bioactive molecules that quench free radicals.…”
Section: Discussionsupporting
confidence: 81%
“…ROT co-exposed with MK-ZnO NPs demonstrated significantly less blue staining in the tissues mentioned above and the whole larvae when compared to the ROT plus UD-ZnO and ROT plus MC-ZnO NPs groups, respectively. This conclusion is validated by a previous investigation that showed that plant biomolecules significantly enhanced cell viability and attenuated DNA damage [ 79 , 80 ]. Biogenic ZnO-NPs are protective due to the activation of antioxidant defense mechanisms or the presence of bioactive molecules that quench free radicals.…”
Section: Discussionsupporting
confidence: 81%
“…Costus woodsonii leaf extract has been successfully used to synthesize narrow-band-gap ZnO-NPs [21]. An important environmental application has been developed by evaluating the antibacterial activity of Terminalia catappa leaf extract in plant-mediated ZnO-NPs and three other ZnO-NPs, and the activity was higher than that of the uncapped ZnO-NPs leaf extract and Terminalia catappa alone [22]. A modern method has been used to extract components from the leaves of Thymus vulgaris by developing a simple hydrothermal method and extracting phytochemicals for ZnO-NPs; the use of thymus leaf extract as a reducing agent containing flavonoids, phenols, and saponins played a significant role in the production of ZnO-NPs [23].…”
Section: Introductionmentioning
confidence: 99%
“…These dyes are characterized by a higher degree of aromaticity, intense color stability, chromophores conjugation, and excellent structural stability, which makes them refractory to degradation. Also, the chemical stability and high temperature resistance features of synthetic dyes inhibit the penetration of light, resulting in decreased dissolved oxygen capacity, which leads to the destruction of aquatic biota [2,3]. Hence, it is very difficult to remove these dyes and pollutants through natural degradation processes.…”
Section: Introductionmentioning
confidence: 99%